Occurrence of leaf spot disease caused by Neopestalotiopsis clavispora on Taxus chinensis in China. Issue 5 (2nd July 2019) - Wang, Rongbo; Chen, Shuzhun; Zheng, Bowen; Liu, Peiqing; Li, Benjin; Weng, Qiyong; Chen, Qinghe
Abstract: Taxus chinensis is a valuable tree with uses for timber, medicinal, ornamental and landscape purposes. Most importantly, it is a source of the anti‐cancer drug paclitaxel. In 2016, needle spot disease was observed on T .  chinensis in Fujian Province of China. Five isolates of similar morphology were isolated from diseased samples. The pathogen was identified as Neopestalotiopsis clavispora based on morphological and cultural characteristics and confirmed by sequence analysis of the internal transcribed spacer region (ITS) and the large subunit ribosomal RNA gene (LSU). The pathogenicity of the isolates was confirmed by fulfilling Koch's postulates. To the best of our knowledge, this is the first report to indicate that the causal agent of needle spot disease on Chinese yew in China is N .  clavispora .